2011
DOI: 10.1182/blood-2010-09-191312
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic and functional role of microRNAs in acute myeloid leukemia

Abstract: IntroductionMicroRNAs are naturally occurring 18-to 25-nucleotide RNAs that are cleaved from 70-to 100-nucleotide hairpin precursors by a complex protein system that includes the RNase III Drosha and Dicer, members of the Argonaute family. 1,2 Mature microRNAs typically hybridize to the 3Ј-untranslated regions of protein-coding messenger RNAs (mRNAs) and cause their post-transcriptional repression and/or degradation in proliferating cells, 1,2 although emerging data indicate that microRNAs can also regulate ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
205
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(207 citation statements)
references
References 113 publications
2
205
0
Order By: Relevance
“…There is accumulating evidence that dysregulation of miRNA expression is involved in various cancers, including hematological malignancies (31)(32)(33)(34). Here, we identified for the first time a CXCR4/let-7a/BCL-XL axis in human AML cells that may be responsible for the chemoresistance observed in the clinical setting.…”
Section: Discussionmentioning
confidence: 75%
“…There is accumulating evidence that dysregulation of miRNA expression is involved in various cancers, including hematological malignancies (31)(32)(33)(34). Here, we identified for the first time a CXCR4/let-7a/BCL-XL axis in human AML cells that may be responsible for the chemoresistance observed in the clinical setting.…”
Section: Discussionmentioning
confidence: 75%
“…Alteration in miRNA gene expression or function can promote cancer initiation and progression in vivo, leading to the recognition that this class of small noncoding RNAs can function as both oncogenes and tumor suppressors (3)(4)(5). Much less is known, however, regarding the role of miRNAs in cancer maintenance.…”
mentioning
confidence: 99%
“…Activation of Toll-like receptors induces production of inflammatory cytokines which promote the survival and proliferation of AML blasts. These genes are down regulated by miR-181 family [16] .…”
Section: Survival Analysismentioning
confidence: 99%
“…Additionally, molecular studies on cytogenetically normal AML patients (CN-AML) showed that CEBPA mutations, which carry favorable prognostic value in CN-AML, have been associated with an upregulation of members of miR-181 family [16] . They integrated gene expression with miRNA expression profile and observed a functional relationship between them.…”
Section: Survival Analysismentioning
confidence: 99%